صور الليل في شعر العرجيّ - يعقوب, عبد الكريم; بيطار, لجين (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
ينشد هذا البحث الكشف عن أبعاد النفس الإنسانية لدى واحد من شعراء العصر الأموي، ويلقي الضوء على بعض التبدّلات التي طرأت على المجتمع الأمويّ، والتي أثّرت تأثيراً واضحاً في أسلوب تفكير الإنسان في ذلك المجتمع، فجعلته يفكّر في أمور أعمق، وأوسع أفقا، تجلّت في مواقفه تجاه الحياة التي تشي بالغربة التي كان يعيشها مع ذاته؛ فبدت ملامح الغربة تظهر في صور الليل في أشعار العرجي، التي اتّسمت بالعمق، والدراية؛ إذ حملت ملامح الفراسة، ومعاني الكشف والاستدلال، فوضّحت تباين النفوس البشرية في العصر الأمويّ، ومدى اختلاف تعاطيها مع الظواهر الكونية. كما أثبتت هذه الصور ظهور النزعة القصصية في الشعر الأمويّ. هذه النزعة التي تضفي جمالا فنيًّا متميّزا، وتفصح عن دواخل إنسانيَّة، ، وتكشف عن رؤيا واعية، وتمدّنا بأحاسيس، ومواقف عاناها الإنسان في العصر الأمويّ. ويبيّن البحث أهمية الصورة في دراسة الشعر، والكشف عن أبعاد القصيدة، وموقف الشاعر من الواقع، وهي أحد المعاييرالفنيّة في الحكم على أصالة التّجربة، وقدرة الشاعر على تشكيلها في نسق يحقّق المعرفة والمتعة لمن يتلقّاها. This research aims to unveil the nature of human spirit as well as it reflects the transformations that took place in the Omayyad society; which had major influence on the people’s mind-set. These changes have been revealed in the deep and sophisticated thinking featuring phenomenal aspect of self-isolation that people lived during the Omayyad’s era. This feature was dominate in the night images of Al Arji’s poetry and it embedded authentic artistic indications that define the poet’s opinion towards several issues related to the concepts of beauty or viciousness. These images mark the emerging of the trend of story-telling in the Omayyad poetry which in turn configure distinctive artistic values and discloses the inner human aspects and the matured vision at that time. These images provide us with different sentiments and phases that people have suffered from during the Omayyad era. This research also highlights the significance of the artistic image as a main tool for the temporary critique thinkers to understand the poem and to unveil the poet’s attitude towards life. This image is are considered as an important standards to assess the poetic experience as well as it indicates the poet capability in passing knowledge and pleasure to the readers.